Nanoagroceuticals & nanophytochemicals - Bhoop, Bhupinder Singh (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This book volume encompasses the recent trends made in the applications of nanoscale tools for diverse constituents of plants and agriculture, particularly in addressing the critical issues related to their safety, efficacy, and efficient and cost-efficient development and production.
OCLC-licensed vendor bibliographic record.
Keywords: Nanobiotechnology; Nanostructured materials; Pharmaceutical biotechnology; Phytochemicals; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; SCIENCE / Biotechnology; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / General